Analysis The Influence Of Trust In Online Store And Perceived Risk Towards Online Repurchase Intention - Vitaloka, Dyah Ayu; , Dr. Ihwan Susila. SE.,M.Si (2016)
The purpose of this study was to determine the effect of trust in the online store and the perceived risk of online purchase intention towards in all consumers who never make repurchases or transactions online. The hypothesis of this study is suspected there was significant trust in the online store and the perceived risk of the online purchase intention. The population in this study was people who never make purchases online from student up with workers. Data were collected from the questionnaires. Purposive sampling method used to select the appropriate sample with 125 respondents. This study uses multiple regression analysis tests (F-test, t test, and test R2). This research resulted in several findings. The first finding is that trust in the online store has significant effect on online repurchase intention. The second is a perceived risk finding did not significantly affect the online repurchase intention. This study suggests that online store owners more interactive and creative in attracting consumers so that consumers believe the products are sold as well as minimizing the risks to be acceptable to consumers.